Pengaruh site design, informativeness, dan security terhadap customer satisfaction online web retailing zalora Indonesia - YUNIA AYU LESTARI HENDRANINGTIYAS; WIBISONO SOEDIONO (Jurnal Bisnis dan Akuntansi, 2015)
The purpose of this research is to analysis how site design, informativeness, and security influence customer satisfaction online web retailing Zalora. The sampling method in the research was convenience sampling and used 100 respondents. Data was used the primary data, and the methods to analyze the data was regression. The result of this research shows that site design, informativeness, and security have positive influence to customer satisfaction.